Patterned flexible graphene sensor via printing and interface assembly. Issue 21 (9th May 2019) - Xue, Tangyue; Yang, Huige; Shen, Bin; Li, Fengyu; Su, Meng; Hu, Xiaotian; Liu, Wentao; Song, Yanlin
Abstract : Multiresolution integrated graphene sensor with microstructures and macropatterns realizes point recognition and wrist movement monitoring. Abstract : Multi-modal, multi-point, and multi-functional integration is the impending pursuit for next generation flexible electronical sensors. Graphene, a carbon sheet 2D material with excellent flexibility and mechanical performance, is endowed with diverse morphological structures, such as fibers, ribbons, films, papers, and aerogels. In this study, we designed and fabricated a flexible graphene sensor integrated with different microstructures and various macropatterns by direct writing printing. The porous serpentine patterns of the graphene aerogels resulted in a multi-dimensional deformation response, while the layered stacked dense-packing graphene ribbon patterns provided good conductivity for efficient signal transmission. The integrated sensors were produced via the cooperation of various macro-patterns and different microstructures with homo-graphene material, which eliminated interface coalescence defects and contact resistance. This methodology has potential application in e-skin, wearable devices, human-machine interactions, and health monitoring devices.